Manajemen Strategis di Dinas Penanaman Modal dan Perizinan Kota Yogyakarta: Analisis Lingkungan Internal dan Eksternal - Endry Putra; Asti Amelia Novita; Pratama, M. Rizky (Jurnal Ilmiah Administrasi Publik, 2022)
The Investment and Licensing Service Agency of Yogyakarta City have received public services awards and has become a pilot of an excellent service in Indonesia. The accuracy of strategic management is one of the dominant factors influencing the success of the Yogyakarta City DPMP in the implementation of public services. This research aims to analyze the internal and external environment that affect the effectiveness of strategic management implementation at the Yogyakarta City Investment and Licensing Office Agency. The research method used in this study is qualitative. The results showed that there were seven keys to the success of the Yogyakarta City DPMP including the existence of new forms of service, the durability of the new service model, effectiveness in achieving goals, service quality, availability of data and information, ease of access to data and information and the actuality of data and information.